Estudo comparativo da migração, integração e diferenciação de células-tronco mesenquimais provenientes de diferentes fontes em tecido retiniano lesado - Paula Castanheira (2009)
To evaluate DAPI (4',6-Diamidino-2-phenylindole) as a nuclear tracer of stem cells migration and incorporation it was observed the pattern of retinal integration and differentiation of mesenchymal stem cells (MSCs) injected into the vitreous cavity of rat eyes with retinal injury. For this purpose adult rat retinas were submitted to laser damage followed by transplantation of DAPI-labeled BM-MSCs grafts and double labeled DAPI and Quantum dot labeled BM-MSCs. To assess a possible DAPI diffusion as well as the integration and differentiation of DAPI labeledBM-MSCs in laser-injured retina, host retinas were evaluated 8 weeks after injury/transplantation. It was demonstrated that, 8 weeks after the transplant, most of the retinal cells in all neural retinal presented nuclear DAPI labeling, specifically in the outer nuclear layer (ONL), inner nuclearlayer (INL) and ganglion cell layer (GCL). Meanwhile, at this point, most of the double labeled BM-MSCs (DAPI and Quantum dot) remained in the vitreous cavity and no retinal cells presented the quantum dot marker. Based on these evidences we concluded that DAPI diffused toadjacent retinal cells while the nano crystals remained labeling only the transplanted BM-MSCs. Therefore, DAPI is not a useful marker for stem cells in vivo tracing experiments since, the DAPI released from dying cells in moment of the transplant are taken up by host cells in the tissue.Quantitative PCR results shows that MSCs survive for at least e weeks,. Also is was possible to observe higher levels of neuroproctetive factors such as BDNF e VEGF.